Finding Critical Element in the Progressive Collapse of RC Structures Using Sensitivity Analysis - Farahani, Ahmad; Kheyroddin, Ali; Sharbatdar, Mohammad Kazem (Salehan Institute of Higher Education, 2018)
Failure of some elements in the structure can play triggering role for beginning of collapse progression. The critical element is the structural element that when it fails, leads to progressive collapse. To find the critical element of the structure, sensitivity analysis should be done. But there are not specific structural criteria for using in sensitivity analysis. In this paper following GSA, UFC 4-023-03 and ASCE guidelines, sensitivity analysis has been modified and applied to find the critical element of a major number of reinforced concrete structures. 1080 3D nonlinear pushdown analyses were done and the results showed that the place of the critical elements differs in different stories and different plan shapes of high rise structures. In the structures with high aspect ratio in height, the critical element of the whole structure is located in the story of 2/3 height of the structure. When the aspect ratio of the structure in plan increases, sensitivity of the columns in the long dimension of the structure become closer to each other.